Design Development of Coffee Roaster with Quality Function Deployment Method - Satria, Fajri Ilham; Saferi, Rozi; Yanto, Asmara (Jurnal Teknik Mesin, 2024)
This research aims to identify and determine the level of consumer needs regarding the coffee roaster and to compile a House of Quality (HOQ) to determine dominant design needs and priority technical characteristics of the machine. The benefit of this research is to be able to develop the coffee roaster and to maximize machine use and time efficiency in roasting coffee. The research method used is the Quality Function Deployment (QFD) method by conducting field surveys aimed at finding out the level of consumer needs by distributing questionnaires and looking for information about what the need to make it easier to roast coffee beans. The location of this research was carried out in several café or coffee shop in Padang City. Based on the column weight, it was found that the strongest priority in the technical response was the design aspect with a value weighting of 38.64, followed by the material criteria aspect with a value weighting of 66.1, then time and energy efficiency with values ​​weighting of 30.34 and 15 respectively.. The design for developing coffee roaster according to consumer needs lies in a more affordable price which makes the use of materials and sizes of horizontal sangria equipment cheaper compared to conventional coffee roasting equipment.